INTEGRATING DIGITAL COMPETENCE IN ADULT EFL LEARNERS: STRATEGIES FOR EFFECTIVE TECHNOLOGY USE - Imaniah, Ikhfi; Zakky, Akhmad; Yuliana, Deni (English Review: Journal of English Education, 2025)
The integration of digital literacy into language learning has been widely explored, yet studies focusing on adult English as a Foreign Language (EFL) learners’ digital competence in academic settings remain limited. Previous research has highlighted general digital literacy frameworks (Reddy et al., 2023; Fadilah, 2023), teacher digital competence gaps (Giannikas et al., 2022), and the positive correlation between digital literacy and language proficiency (Wahyuddin et al., 2024). However, these studies have not specifically examined how adult EFL learners navigate digital literacy challenges, particularly in critical evaluation of online resources and cybersecurity awareness. This study aims to assess the digital competence of adult EFL learners, focusing on five key dimensions: general digital competence, technology integration in language learning, digital literacy and skills, digital communication and collaboration, and online safety. Using a structured questionnaire administered to 56 university students, the findings indicate that while students demonstrate strong proficiency in basic digital tasks and language learning applications (71% overall digital competence score), they struggle with critically evaluating online resources and cybersecurity practices. These results emphasize the need for structured pedagogical strategies, including targeted digital literacy training and collaborative learning environments, to enhance EFL learners’ technological integration skills. This study contributes to the effective implementation of digital literacy in EFL education by addressing the specific challenges faced by adult learners, ultimately fostering their linguistic and digital proficiency in academic and professional contexts. The findings imply that EFL programs should include targeted digital literacy education that tackles critical thinking and online safety. Strengthening these areas will enable adult learners to effectively navigate digital settings, promoting academic achievement as well as lifetime digital involvement.